Establishing Similarities and Differences among the Self-Reported Academic Integrity of Australian Occupational Therapy Undergraduate and Graduate-Entry Master 's Students - Ted Brown; Helen Bourke-Taylor; Stephen Isbel; Louise Gustafsson; Carol McKinstry; Alexandra Logan (Scholarworks @ WMU, 2019)
Background: Research into the prevalence of dishonest academic behaviors suggests that such behaviors may be extensive in higher education. This study investigated the academic integrity of Australian occupational therapy students and compared the perspectives of undergraduate (UG) and graduate-entry master's (GEMs) students. Method: Students from five Australian universities (701; response rate 35%; 72.5% female) completed five standardized scales: (a) Academic Dishonesty Scale; (b) Academic Dishonesty in the Classroom Setting Scale; (c) Academic Dishonesty in the Clinical/Practice Education Setting Scale; (d) Academic Dishonesty Tendency Scale; and (e) Perceived Academic Sources of Stress. One-way analyses of variance were conducted to compare the scores of the UG and GEMs students. Results: No significant differences were found on the UG (n = 609) and GEMs (n = 92) students' self-reported scores in academic dishonesty in the classroom and practice education settings. Significant differences were noted between the UG and GEMs students on self-reported tendency toward dishonesty in providing appropriate references, on workload and examinations, and self-perception. Overall, low rates of academic integrity breaches were reported by occupational therapy UG and GEMs students, but they are still present. Conclusion: Occupational therapy UG and GEMs students report good levels of academic integrity in the classroom and practice education settings, although areas of concern in academic integrity were identified. Educators should facilitate the development and awareness of academic integrity among UG and GEMs occupational therapy students.